ANALISIS PENYEBAB KELUHAN NECK PAIN PADA PEKERJA DI PABRIK SEPATU DAN SANDAL KULIT KURNIA DI KOTA SEMARANG - Aulia Gita Safitri; Baju Widjasena; Bina Kurniawan (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Neck pain often occurs due to an awkward posture in activities such as sitting and bowing for long periods. The types of activities studied are sole cutting, sole mounting, and shoe gluing. These activities were carried out in a sitting position with small chairs or stools, bending, and bowing. Working activities at Kurnia Leather Shoes and Sandals Factory have a long duration, and tend to be static and repetitive so that workers may experience neck pain complaints. The purpose of this study is to analyze the causes of neck pain complaints on workers in Kurnia Leather Shoes and Sandals Factory in the Municipality of Semarang. The research is conducted qualitatively. Data analysis was done by descriptive analysis. Research subjects are 5 workers of Kurnia Leather Shoes and Sandals Factory. The triangulation tool in this research is the assessment result of Base Risk Identification of Ergonomic Factor (BRIEF) method. The informants interviewed were men with age range above 35 years old. Based on the assessment by BRIEF Survey method all high-risk informants, but based on the results of in-depth interviews obtained most informants experienced neckpain complaints. Neck pain complaints perceived by workers varying are aches, pains, and dizziness. Informants who do not feel the complaint is due to the activity that has become a habit. To reduce neck pain complaints, should stretch the muscles before and after work.